DIMENSI SERVICE EXPERIENCE DALAM MEMBENTUK REPURCHASE INTENTION PADA MD CLINIC BY LAZETA SKIN CARE - Aghnia, Nisa; Wibowo, Lili Adi (Journal of Business Management Education (JBME), 2017)
Purpose - to find out the description of the level of service, experience and repurchase intention in patients MD Clinic by Lazeta Skin Care Branch Kopo and obtained the findings of the magnitude of the influence of dimensions of service experience in shaping the repurchase intention in patients MD Clinic by Lazeta Skin Care Branch Kopo.Design/methodology/approach - This type of research used are descriptive, verifikatif. The method used was explanatory survey with simple random sampling techniques and sample number of 200 respondents. Data analysis technique used is a structural model with equal tools computer software SPSS AMOS 22.0.Findings - Based on the research done as a whole , the size of the influence each variable latent directly ( standardize direct effect ) or indirectly ( standardize indirect effect and the total effect ( standardizes total effect that variable dimensions service experience have a direct influence in forming repurchase intention of 0.769 . Service experience as variables influential dominant must remain controlled directly by company Originality / value - The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the studyÂ Keywords: service experience, repurchase intention, skin care, beauty careÂ Article Type: Research Paper